Age-Related Utilization of Thrombus Aspiration in Patients With ST-Segment Elevation Myocardial Infarction: Findings From the Improving Care for Cardiovascular Disease in China Project - Qu, Yang-Yang; Zhang, Xiao-Guo; Ju, Cheng-Wei; Su, Ya-Min; Zhang, Rui; Zuo, Wen-Jie; Ji, Zhen-Jun; Chen, Li-Juan; Ma, Gen-Shan (Frontiers in Cardiovascular Medicine, 2022)
Background There are some controversies on the utilization and benefits of thrombus aspiration in patients with ST-segment elevation myocardial infarction (STEMI). However, a few studies investigated this issue and the age-associated effects among the large population in China. Hence, we aimed to figure out the age-associated utilization and in-hospital outcomes of thrombus aspiration to improve therapeutic decisions in clinical routine. Methods We retrospectively recruited 13,655 eligible STEMI patients from the database of the Improving Care for Cardiovascular Disease in China-Acute Coronary Syndrome project. These subjects were allocated into primary percutaneous coronary intervention (PPCI)-only group and thrombus aspiration group after being subdivided into three age groups (G21−50, G51−75, and G76−95). After 1:1 propensity score matching for PPCI-only and thrombus aspiration groups, a total of 8,815 matched patients were enrolled for the subsequent analysis. The primary outcome was in-hospital cardiovascular death, and the key safety outcome was in-hospital stroke. Results We observed that the ratio of STEMI patients undergoing thrombus aspiration to PPCI-only reduced with aging. For patients ≤ 75 years, the culprit lesion suffered from thrombus aspiration was mainly located in the left anterior descending branch, and left-ventricular ejection fraction (LVEF) was lower (G21−50: 54.9 ± 8.9 vs. 56.0 ± 8.7%, P = 0.01; G51−75: 53.9 ± 9.6 vs. 54.8 ± 9.0%, P = 0.001) and the rate of regional wall motion abnormality was higher (G21−50: 75.7 vs. 66.5%, P < 0.001; G51−75: 75.4 vs. 69.1%, P < 0.001) in the thrombus aspiration group. By contrast, for patients > 75 years, the right coronary artery was the predominant culprit lesion undergoing thrombus aspiration, LVEF (63.1 ± 10.5 vs. 53.1 ± 9.5%, P = 0.985) and the regional wall motion abnormality (79.2 vs. 74.2%, P = 0.089) were comparable between the two treatment groups. Thrombus aspiration neither reduced the in-hospital risk of cardiovascular death, all-cause death, recurrent myocardial infarction, acute stent thrombosis, heart failure, cardiogenic shock, and sudden cardiac arrest nor increased stroke risk compared with the PPCI-only group. However, after adjustment for age, thrombus aspiration presented the tendency to reduce the incidence of sudden cardiac arrest (4.9 vs. 2.5%, P = 0.06) and in-hospital cardiovascular death at 3 days (hazard ratio 0.46; 95% CI, 0.20–1.06; log-rank P = 0.08) in G76−95 group and tended to increase the incidence of heart failure in G51−75 (5.7 vs. 6.9%, P = 0.07). Conclusion The thrombus aspiration neither significantly reduced the in-hospital incidence of major adverse cardiac events nor increased stroke risk. However, it might play a protective role in reducing in-hospital sudden cardiac arrest and increasing survival from cardiovascular death at 3 days for the elderly.